Analisis Keberadaan Mikroplastik Pada Air dan Sedimen Di Danau Limboto - Basalama, Muhamad Tri Rezki; Kunusa, Wiwin Rewini; Suleman, Nita (Jambura Journal of Chemistry, 2025)
This study aims to identify the type and abundance of microplastics in water and sediment in Lake Limboto. Sampling was conducted at four points using purposive sampling method. Analysis of the type and abundance of microplastics was carried out with a binocular microscope (4Ã—10 magnification) and FT-IR spectroscopy. The results showed the presence of three types of microplastics based on shape, namely fiber, film, and fragment, as well as two types of polymers, namely polyvinyl chloride and polyamide. The total abundance of microplastics in water samples was 940 particles/m³, with the highest abundance at point 2 (290 particles/m³) and the lowest at point 1 (170 particles/m³). In sediment samples, the total abundance of microplastics was 2400 particles/kg, with the highest abundance at point 2 (660 particles/kg) and the lowest at point 1 (540 particles/kg). These results show significant distribution and variation of microplastic abundance in Lake Limboto.